Development of Multicultural-Based Illustrated Story Books for Children - Diplan; Wahyu; Manesa (Proceeding International Conference on Education, 2024)
This study aims to develop a multicultural-based picture story book for children. The relocation of the nation's capital to the island of Kalimantan has become a stimulus for increasing population movement from various regions and increasing the diversity of Indonesian culture to Kalimantan. Understanding diversity is a must for both indigenous Kalimantan people and domestic migrants communities. The type of research used in this study is the research and development method. The development model used is the 4D model from Thiagarajan, Semmel and Semme including the definition, design, development, and dissemination stage. This study only reaches the development stage by conducting a media feasibility test through expert appraisal, student responses and teacher responses. The research subjects selected were grades 3 and 4 and teacher. Material aspects in the form of aspects of cultural representation and precision, aspects of interaction and multicultural values ​​and aspects of presentation and suitability, media validation in the form of aspects of content and narrative, visual and design aspects, aspects of representation and diversity, aspects of education and development, student response questionnaires and teacher responses. Based on media expert validation, it got 4.91 with the category of "Very Good", material expert validation got a score of 4.87 with the category of "Very Good", the average score of the overall student response got a score of 4.7 with the category of "Very Good", while for the average score of teacher response 3.8 with the category of "Good". It can be concluded that the illustrated story book media for children is suitable for use in learning in Elementary Schools.